Vessel Wall Enhancement and Focal Cerebral Arteriopathy in a Pediatric Patient with Acute Infarct and COVID-19 Infection - Gulko, E.; Overby, P.; Ali, S.; Mehta, H.; Al-Mufti, F.; Gomes, W. (American Journal of Neuroradiology, 2020)
SUMMARY: Herein, we report the findings of intracranial arterial wall enhancement, consistent with focal cerebral arteriopathy–inflammatory type, in a child presenting with acute infarct in the setting of coronavirus disease 2019 (COVID-19) infection. To our knowledge, this report provides the first description of vessel wall imaging findings in COVID-19-associated acute stroke.COVID-19coronavirus disease 2019FCAfocal cerebral arteriopathySARS-CoV-2Severe Acute Respiratory Syndrome coronavirus 2VWIvessel wall imaging